2016
DOI: 10.1088/2053-1583/3/2/025009
|View full text |Cite
|
Sign up to set email alerts
|

Examining the impact of multi-layer graphene using cellular and amphibian models

Abstract: OATAO is an open access repository that collects the work of Toulouse researchers and makes it freely available over the web where possible. This is an author-deposited version published in : http://oatao.univ-toulouse.fr/ Eprints ID : 16789To link to this article : AbstractIn the last few years, graphene has been defined as the revolutionary material showing an incredible expansion in industrial applications. Different graphene forms have been applied in several contexts, spreading from energy technologies an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 46 publications
2
16
0
Order By: Relevance
“…As evidenced in earlier studies on raw CNPs [19,20,37], the dissections revealed the presence of dark agglomerates in the digestive tract and in gills of larvae exposed to each CNP compared to the NC larvae ( Fig. 3).…”
Section: Macro-observations Of Dissected Larvaesupporting
confidence: 74%
See 1 more Smart Citation
“…As evidenced in earlier studies on raw CNPs [19,20,37], the dissections revealed the presence of dark agglomerates in the digestive tract and in gills of larvae exposed to each CNP compared to the NC larvae ( Fig. 3).…”
Section: Macro-observations Of Dissected Larvaesupporting
confidence: 74%
“…5. B) [37]. In our exposure conditions, Xenopus larvae ingest their feces and suspended matter continuously over the 24 h of the medium renewal, leading to a kind of sediment composed of a mixture of agglomerated CNPs and organic matter in the crystallizing dishes.…”
Section: State Of Dispersionmentioning
confidence: 99%
“…-4 -Only few and quite recent studies have been focused on understanding the impact of graphene or FLG on mammalian cells, and most of them were investigating the impact of graphene on cell lines with the exception of a study by Russier et al that showed that FLG was able to selectively kill pathogenic monocytes from myelomonocytic leukemia patients. [17][18][19] However, to the best of our knowledge, no study has been looking into the impact of FLG on primary lymphocytes and on their autophagic activity. As these cells are key players in adaptive immunity, it appears essential to understand how FLG could interact with them.…”
Section: Introductionmentioning
confidence: 99%
“…There was a lack of studies on the effects of graphene and reduced graphene oxide on ciliates, as well as characterization of graphene oxide NMs used in studies with ciliates. Standardized test protocols according to the International Organization for Standardization (ISO), the Organisation for Economic Co‐operation and Development (OECD), and the US Environmental Protection Agency (USEPA) were used in one study with bacteria , 2 studies with algae , 4 with freshwater invertebrates , 2 with a freshwater vertebrate‐fish , and 2 with an amphibian (Mottier et al was not included in the SSD analysis). Descriptions of experimental methodologies (other than USEPA, OECD, or ISO) were available in all publications.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies have reported that exposure of fish embryos to graphene oxide can induce oxidative stress, delayed hatching, morphological changes, and apoptosis . Muzi et al showed that multilayer graphene had no effect on mortality (0–50 mg/L) of Xenopus laevis larvae; however, it managed to cause growth inhibition at concentrations of 10 and 50 mg/L.…”
Section: Resultsmentioning
confidence: 99%